1997
DOI: 10.1515/cclm.1997.35.7.517
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase Activity in Lymphocytes and Polymorphonuclear Cells of Diabetic Patients

Abstract: Copper-zinc Superoxide dismutase (Cu,Zn-superoxide dismutase) activity was evaluated in lymphocytes and polymorphonuclear cells of insulin-dependent (n = 33) and non-insulin-dependent (n = 34) diabetic patients. A commercial method for the measurement of Superoxide dismutase activity was adapted for use on a discrete analyser and evaluated for interference by other antioxidants with Superoxide anion-scavenging properties. In comparison to healthy control subjects (n = 32), a significantly lower Cu,Zn-superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…SOD and CAT are the two major scavenging enzymes that remove toxic free radicals. Previous studies have reported that the activity of SOD is low in diabetes mellitus (Vucic et al, 1997). Administration of n-BF increased the activity of these enzymes and may help to control free radical, as n-BF has been reported to be rich in flavonoids, a well known antioxidant (Middleton et al, 2000) which scavenges the free radical generated during diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…SOD and CAT are the two major scavenging enzymes that remove toxic free radicals. Previous studies have reported that the activity of SOD is low in diabetes mellitus (Vucic et al, 1997). Administration of n-BF increased the activity of these enzymes and may help to control free radical, as n-BF has been reported to be rich in flavonoids, a well known antioxidant (Middleton et al, 2000) which scavenges the free radical generated during diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…SOD and CAT are the two major scavenging enzymes that remove toxic free radicals in vivo. Previous studies have reported that the activity of SOD is low in diabetes mellitus (Vucic et al, 1997;Feillet-Coudray et al, 1999). A decrease in the activity of these antioxidants can lead to an excess availability of superoxide anion O 2 − and hydrogen peroxide in biological systems, which in turn generate hydroxyl radicals, resulting in initiation and propagation of lipid peroxidation (Kumuhekar and Katyane, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic state is shown to be associated with depletion of antioxidants [25]. Vucic et al [26] reported that the activity of SOD is low in diabetes mellitus. Decreased catalase activity in plasma and tissues of streptozotocin diabetic rats, may be due to increased utilization to scavenge the toxic products of lipid peroxidation or decreased availability of H 2 O 2 , the substrate for catalase.…”
Section: Changes In the Level Of Enzymatic Antioxidants In Diabetic Ementioning
confidence: 99%